Polyoxypregnane Glycosides from the Roots of Marsdenia tenacissima and Their Anti-HIV Activities - Pang, Xu; Kang, Li-Ping; Fang, Xiao Mei; Zhao, Yang; Yu, He-Shui; Han, Li-Feng; Li, Hai-Tao; Zhang, Li-Xia; Guo, Bao-Lin; Yu, Li-Yan; Ma, Bai-Ping (Planta Medica, 2017)
A continuous phytochemical study on the roots of Marsdenia tenacissima led to the isolation and identification of 13 new polyoxypregnane glycosides named marstenacissides B10–B17 (1, 2, 4, 7, 8, 11, 12, and 14) and marstenacissides A8-A12 (3, 9, 10, 13, and 15) in addition to two known polyoxypregnane glycosides marsdenosides M and L (5 and 6). Their structures were established by spectroscopic techniques and by comparison with the reported data in the literature. Moreover, the anti-HIV activities of these isolates and the previous isolated marstenacissides A1–A7 and B1–B9 were assessed, some of which exhibited slight or negligible effects against HIV-1.
Keywords: Marsdenia tenacissima; Asclepiadaceae; polyoxypregnane glycoside; marstenacisside; anti-HIV; antiviral activity